Antiplatelet agents in the secondary prevention of vascular events in adults undergoing percutaneous coronary intervention: Cost-effectiveness, budget impact and research priorities - Russell, Erin Leigh (University of Ottawa (Canada), 2011)
This thesis was undertaken to investigate the cost-effectiveness of various antiplatelet regimens used in the secondary prevention of vascular events in adults undergoing percutaneous coronary intervention (PCI). Analyses include the first economic evaluation to evaluate three antiplatelet regimens (clopidogrel + ASA, ticlopidine + ASA, and ASA alone) for the PCI indication from the perspective of the Canadian provincial/territorial healthcare payer, budget impact analyses investigating potential consequences of changing prescribing patterns, and a value of information analysis indicating future research priorities. Results demonstrate that, for a population of patients undergoing PCI at age 60, one year of antiplatelet therapy with ticlopidine + ASA, followed by lifetime ASA therapy, dominates clopidogrel + ASA therapy due to lower costs and better health outcomes (ICER = $523.44 vs. ASA alone). The clinical effectiveness of ticlopidine is proven to be the most uncertain variable in the model, and further clinical research is recommended.
Keywords: Health Sciences, Epidemiology.